2007
DOI: 10.1523/jneurosci.3178-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

In VivoAnalysis of Ascl1 Defined Progenitors Reveals Distinct Developmental Dynamics during Adult Neurogenesis and Gliogenesis

Abstract: In the adult mammalian brain, new neurons and glia are continuously generated but molecular factors regulating their differentiation and lineage relationships are largely unknown. We show that Ascl1, a bHLH (basic helix-loop-helix) transcription factor, transiently labels neuronal and oligodendrocyte precursors in the adult brain. Using in vivo lineage tracing with inducible Cre recombinase, we followed the maturation of these precursors in four distinct regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
146
4
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(166 citation statements)
references
References 58 publications
(79 reference statements)
14
146
4
2
Order By: Relevance
“…CreERT2 (Ascl1 tm1(Cre/ERT2)Jejo /J ) mice (Kim et al, 2007), obtained from The Jackson Laboratory, and CAG floxStop-tdTomato (Ai14) (B6;129S6-Gt(ROSA)26Sor tm14(CAG-tdTomato)Hze /J) conditional reporter line (Madisen et al, 2010) CreERT2 ;CAG floxStopTom line. Mice were anesthetized and decapitated at 21-56 d post TAM induction (dpi), and transverse slices were prepared as described previously (Marín-Burgin et al, 2012).…”
Section: Mice Ascl1mentioning
confidence: 99%
See 1 more Smart Citation
“…CreERT2 (Ascl1 tm1(Cre/ERT2)Jejo /J ) mice (Kim et al, 2007), obtained from The Jackson Laboratory, and CAG floxStop-tdTomato (Ai14) (B6;129S6-Gt(ROSA)26Sor tm14(CAG-tdTomato)Hze /J) conditional reporter line (Madisen et al, 2010) CreERT2 ;CAG floxStopTom line. Mice were anesthetized and decapitated at 21-56 d post TAM induction (dpi), and transverse slices were prepared as described previously (Marín-Burgin et al, 2012).…”
Section: Mice Ascl1mentioning
confidence: 99%
“…In particular, the astrocyte-specific glutamate transporter (GLAST) is expressed in GFAP ϩ astrocytes and neural stem cells (Type 1), and it has allowed targeting fluorescent reporters to identify postnatal and adult hippocampal neurogenesis (Mori et al, 2006;Ninkovic et al, 2007;Colak et al, 2008;Temprana et al, 2015). Similarly Ascl1, a bHLH transcription factor involved in neuronal differentiation and present in Type 1 and Type 2 cells, has also been used to characterize and manipulate adult neurogenesis (Kim et al, 2007(Kim et al, , 2011Andersen et al, 2014;Mich et al, 2014). While several laboratories have already incorporated these tools for the study of adult neurogenesis, a detailed morpho-functional characterization as a function of neuronal age has never been done.…”
Section: Introductionmentioning
confidence: 99%
“…In this labeling protocol, the majority of BrdUretaining cells are highly proliferative progenitors (type 2 cells), and the combination with immunostaining for cell-type-specific markers enables the progenitor population to be sorted into two stages. Neural progenitors in the former stage (type 2a) and the latter stage (type 2b) can be identified by their expression of Ascl1 (Kim et al, 2007) and Tbr2 (Hodge et al, 2008), respectively. In Sox21 Ϫ/Ϫ mice, the number of BrdU and Ascl1 double-positive cells was significantly increased (Fig.…”
Section: Cifically Impaired In Sox21mentioning
confidence: 99%
“…The neurogenic functions of Ascl1 and Ngn2 are predicted to be conserved in adult hippocampal neurogenesis due to their continued expression in the adult DG (Kim et al, 2007;Ozen et al, 2007). However, this The 284 sites from the Sox21 ChIP sequencing data and the 301 sites from the Sox2 ChIP sequencing data were determined as described in Materials and Methods.…”
Section: Essential Role Of Sox21 During Adult Neurogenesismentioning
confidence: 99%
“…Interestingly, the mouse cortex contains also a large fraction of oligodendrocyte precursors cells that are tightly associated with neurons and do not synthesize Mbp (Trotter et al, 2010). Fate-mapping studies in the mouse showed that although these cells are mostly quiescent, they can be activated to divide and can give rise to oligodendrocytes, to neurons in the piriform cortex, and also to astrocytes (Kim et al, 2007;Dimou et al, 2008;Rivers et al, 2008;Zhao et al, 2009). These cells, which have processes that contact neurons, were variably referred to as polydendrocytes or more generally as OPCs in the mouse and rat (Wolswijk and Noble, 1989;Nishiyama et al, 1999Nishiyama et al, , 2009Hermann et al, 2010).…”
Section: Olig2 Cells In the Parenchyma Of The Telencephalonmentioning
confidence: 99%